2005
DOI: 10.1177/15648265050262s213
|View full text |Cite
|
Sign up to set email alerts
|

Improved Effect of School Meals with Micronutrient Supplementation and Deworming

Abstract: Since 2003, 4 states in India, namely, Gujarat, Andhra Pradesh, Karnataka, and Tamil Nadu covering approximately 30 million schoolers have adopted the "Gujarat Model."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Gopaldas et al reported a decrease in night blindness and vitamin A deficiency from 67% to 34%, as an impact of improved mid day meal program in Gujarat. 12 It may be concluded that children who presented with conjunctival xerosis at base line, some of them advanced to the stage of Bitot's spot due to lack of therapeutic intervention, whereas reduction in prevalence of conjunctival xerosis occurred as an impact of the mid day meals.…”
Section: Discussionmentioning
confidence: 97%
“…Gopaldas et al reported a decrease in night blindness and vitamin A deficiency from 67% to 34%, as an impact of improved mid day meal program in Gujarat. 12 It may be concluded that children who presented with conjunctival xerosis at base line, some of them advanced to the stage of Bitot's spot due to lack of therapeutic intervention, whereas reduction in prevalence of conjunctival xerosis occurred as an impact of the mid day meals.…”
Section: Discussionmentioning
confidence: 97%
“…In the last 10 years, the effects of deworming have been suggested to be improved by synergistic effects with other interventions such as hygiene promotion, iron or vitamin A supplementation and/or feeding programmes (Tanumihardjo, Permaesih et al . 2004; Gopaldas 2005; Nga, Winichagoon et al . 2009; Haque, Ahmed et al .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of night blindness and Vitamin A deficiency reduced from 67 to 34 percent. 15 However, some authors argue that many of the nutrition studies of school lunch programme are controlled trials in which many components of the interventions are closely managed and hence the external validity of these studies for programme implemented in the field is often difficult to ascertain. 16 While the delivery of mid-day meal in schools was initially shrouded in operational difficulties, it was debated that the programme is difficult to scale by government staff and should be handed over to NGOs for better implementation.…”
Section: Malnutrition and Nutrition Specific Interventionsmentioning
confidence: 99%